Strategic decisions on bilateral bidding behavior: evidence from a wholesale electricity market - Moutinho, Vítor F (2018)
This article analyzes the strategic bilateral bidding behavior in the Spanish electricity wholesale market (OMEL). The collection of data includes information regarding weekly averages of spot prices, the quantity bid in the wholesale market, the quantities purchased in the wholesale market and sold in the open market, and the behavior of conduct parameters for the period from January 2002 to April 2007 for the four largest firms of the Spanish electricity market: Endesa, Iberdrola, Unión Fenosa and Hidrocantábrico. This article employs the New Empirical Industrial Organization approach. The empirical analysis was based on the autoregressive distributed lag approach to cointegration and on the Toda–Yamamoto Granger causality tests to validate the standard version of the theoretical formulation of the standard Cournot model, and its theoretical extension, to encompass the hypothesis of the presence of bid interdependence for electricity quantities sold and bought in the Spanish electricity wholesale market. The results of cointegration and causality analysis reinforce the empirical results of the extended Cournot model with the inclusion of the two main bidding variables that solved the optimization problem of profit maximization for each of the four firms analyzed.